ANALISIS PENGARUH PENERAPAN STRATEGI BAURAN PEMASARAN DAN PROGRAM CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS KONSUMEN PADA PRODUK COKRO TELA CAKE YOGYAKARTA - , GLADYS BUNGA JELITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cokro Tela Cake, a pioneer manufacturer that produces tela cake in Yogyakarta continue to make improvements on implementing Customer Relationship Management (CRM) programs and marketing mix strategies to achieve customer satisfaction and loyalty in the midst of intense competition. This study aims to determine the effect of the implementation of CRM programs and marketing mix strategy towards customer satisfaction and loyalty, identify the dominant variables that affect customer satisfaction and loyalty and set up marketing programs suggestions based on the analysis that has been done. Analyses were performed using Structural Equation Modeling (SEM) using LISREL software 8:30. Respondents involved in this study were 120 respondents with a simple random sampling method. The early models that has been set up compiled four latent variables include CRM program, marketing mix strategy, customer satisfaction and customer loyalty. Models that had been developed then tested for their suitability through Goodness of Fit test. The final model in this study has three latent variables : BPCRM (marketing mix and CRM), customer satisfaction and customer loyalty. Hypothesis test results of the final model showed that BPCRM variables significantly influence consumer satisfaction and consumer satisfaction have a significant effect on consumer loyalty. The most dominant variables is X1 (friendliness of employees). Suggestions for improving marketing programs are that the company should updates their social media and website routinely and holding some activities which ever undertaken such Festivall Tela.